PENGARUH PARTISIPASI PEMAKAI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI DENGAN KEMAMPUAN PEMAKAI SEBAGAI VARIABEL MODERASI - Artanaya, Putu Yoga; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2016)
The purpose of this research is to know the influence of the participation of the users of accounting information system on performance with the capability of users as variables moderation. This research was conducted on the All-round Cooperative Efforts in district of East Denpasar. Sampling of the research is with the method of probability sampling techniques with simple random sampling. The data collected using the method of survey with questionnaire technique. Respondents from the research as much as 85 employees who directly using accounting information systems in his work. Moderating Regression Analysis (MRA) is used as the data analysis techniques. Based on the results of the analysis it was found that the participation of the wearer of positive effect on performance information system accounting. The ability of the user is able to strengthen the relationship of user participation on performance of accounting information systems. The ability of the user is pure moderators.
Keywords: user participation, accounting anformation system performance, user capabilities